2019
DOI: 10.1186/s12879-019-4706-8
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and determinants of Klebsiella species bloodstream infection in the western interior of British Columbia, Canada

Abstract: BackgroundKlebsiella species are among the most common causes of bloodstream infection (BSI). However, few studies have evaluated their epidemiology in non-selected populations. The objective was to define the incidence of, risk factors for, and outcomes from Klebsiella species BSI among residents of the western interior of British Columbia, Canada.MethodsPopulation-based surveillance was conducted between April 1, 2010 and March 31, 2017.Results151 episodes were identified for an incidence of 12.1 per 100,000… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…For Klebsiella spp. BSIs, a study from Olmsted county (Minnesota, USA, 1998–2007) reported a 28-day case fatality risk of 14% with associated mortality rate of 1.6 deaths/100,000 person-years [ 41 ], and a study from western interior (BC, Canada, 04/01/2010–03/31/2017) identified a 30-day case fatality risk of 18% and a mortality rate of 2.2 deaths/100,000 person-years [ 42 ]. A study from Calgary (Alberta, Canada, 2000–2006) evaluating Pseudomonas aeruginosa BSIs reported an in-hospital case fatality risk of 29% with a mortality rate of 1.0 deaths/100,000 person-years [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…For Klebsiella spp. BSIs, a study from Olmsted county (Minnesota, USA, 1998–2007) reported a 28-day case fatality risk of 14% with associated mortality rate of 1.6 deaths/100,000 person-years [ 41 ], and a study from western interior (BC, Canada, 04/01/2010–03/31/2017) identified a 30-day case fatality risk of 18% and a mortality rate of 2.2 deaths/100,000 person-years [ 42 ]. A study from Calgary (Alberta, Canada, 2000–2006) evaluating Pseudomonas aeruginosa BSIs reported an in-hospital case fatality risk of 29% with a mortality rate of 1.0 deaths/100,000 person-years [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, KP is the second most common cause of gram-negative bacteremia, following Escherichia coli (E. coli) ( Cubero et al., 2018 ; Hyun et al., 2018 ). The estimated incidence rate of Klebsiella pneumoniae bacteremia (KPB) was increased from 10.2 to 18.7 per 100 000 inhabitants in a region of Canada ( Pépin et al., 2010 ), and the reported mortality rate of KPB varied widely from 11% to 81% in most studies ( Chang et al., 2015 ; Imai et al., 2019 ; Reid et al., 2019 ; Falcone et al., 2020 ; Balkan et al., 2021 ; Meng et al., 2022 ). It is important to accurately estimate the mortality rate of KPB to best define the infectious disease, and it can accurately convey prognosis and improve the guidance to control this disease.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence case of Klebsiella oxytocainduced keratitis is far less than those of blood steam infections. 11 As far as our knowledge, there is only one case that was reported worldwide before this case. 4 In this case report, the isolated Klebsiella oxytoca strain was resistant to ampicillin, cefepime, chloramphenicol, and gentamicin.…”
Section: Discussionmentioning
confidence: 85%